MACRO- AND MICROSTRUCTURE OF HUMAN FETUS CEREBELLUM AT THE 13-14TH WEEKS OF INTRAUTERINE DEVELOPMENT - Shkolnikov, V.S.; Zalevskiy, L.L.; Kyselova, T.M.; Gnenna, V.O. (World of Medicine and Biology, 2019)
The study was performed to establish the structure of the vermis and cerebellum hemispheres macrometric parameters, as well as morphometric parameters and cytoarchitectonics of the human cerebellum on the 13th-14th weeks of fetal development. The anatomic-histological, immunohistochemical and morphometric study was carried out on the vermis and hemispheres of the cerebellum in 12 human fetuses with a gestation term of 13-14 weeks without abnormalities of the central nervous system, which were obtained as a result of a late abortion in the regional pathologist bureau of Vinnytsia. The study found: the transverse size of the cerebellum, longitudinal dimensions, height and transverse size of the cerebellum right and left hemisphere; transverse, longitudinal size and height of the vermis, as well as mass of the cerebellum. It is established that in the histo-cytoarchitectonics of the cerebellum hemispheres, there are three layers: the ventricular zone, the intermediate zone, the cortical zone, which in turn is divided into internal granular, molecular and external granular layers. In the course of the research it was established: the ventricular zone of the right cerebellum has the smallest thickness, and the intermediate zone has the largest thickness; the intermediate zone of the left cerebellum has the greatest thickness, and the ventricular zone has the smallest thickness; the smallest density of neural stem cells is observed in the molecular zone, and the largest is in the ventricular zone; more intensive proliferation of neural stem cells present in the ventricular zone, and less intense - in the intermediate zone; starting from the ventricular zone, the radial glial cells fibers pass through all layers of the cerebellum to the external granular layer in the radial direction; the expression of Synaptophysin is present in all layers of the cerebellum. Thus, the macrometric parameters of the cerebellum formations of 13-14 weeks fetuses are established.
Keywords: cerebellum vermis; cerebellum hemispheres; morphometric parameters; radial glia; intrauterine development